1991
DOI: 10.1192/s0007125000292027
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Carers of Dementia Sufferers

Abstract: Recent research shows that the demands of the caregiving role are experienced differently by men and women. Both the subjective and the objective strain and burden appear to be greater in female carers of dementia sufferers, and factors that influence this include differences in role expectations and coping strategies. These findings have implications for the provision of services for dementia sufferers and their carers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
23
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 28 publications
9
23
0
2
Order By: Relevance
“…Harper and Lund (1990) found wife carers particularly strained by symptoms related to personality change, and husbands by symptoms related to disorientation. Here no gender dierence was found in overall caregiving task involvement, consistent with Enright (1991) and Morris et al (1991), although wives were more involved in household chores, with husbands more involved in`managerial' tasks. But, overall, neither dependants' behaviour nor actual caregiving workload seemed to determine the wives' greater strain.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Harper and Lund (1990) found wife carers particularly strained by symptoms related to personality change, and husbands by symptoms related to disorientation. Here no gender dierence was found in overall caregiving task involvement, consistent with Enright (1991) and Morris et al (1991), although wives were more involved in household chores, with husbands more involved in`managerial' tasks. But, overall, neither dependants' behaviour nor actual caregiving workload seemed to determine the wives' greater strain.…”
Section: Discussionsupporting
confidence: 68%
“…Poor morale, poor general mental health, perceived strain and depression have been reported (Cohen and Eisdorfer, 1988;Dura et al, 1991) with objective ratings of speci®c psychiatric disorders, especially depression, varying between 14% and 45%. Signi®cantly higher levels of strain and distress have usually been found in female carers (reviewed by Morris et al, 1991 andCollins, 1992). Greater subjective burden among women carers has been con®rmed in a large population-based survey (Grafstrom et al, 1994).…”
mentioning
confidence: 97%
“…A poor previous relationship, an older dependant, being coresident, a child rather than a spouse carer, being female, younger or employed, the caregivers themselves being disabled and coping strategies characterized by high levels of expressed emotion are proposed as risk factors for adverse caregiver outcomes (Gilleard et al, 1984;George and Gwyther, 1986;Zarit et al, 1986;Eagles et al, 1987;Morris et al, 1988a,b;Braithwaite, 1990;Bledin et al, 1990;Morris et al, 1991;Jones and Peters, 1992;Yeatman et al, 1993). Potential protective factors include access to a con®ding relationship, an instrumental approach to the provision of care, ascribing the subject's dependency and behaviour to the disease (and not the relationship), the capacity to disengage from the caregiving role and the ability to ®nd meaning in, and have feelings of maintaining control of the caregiving situation (Zarit et al, 1986;Kinney and Stephens, 1989;Morris et al, 1991;Hadjistavropoulos et al, 1994;Livingstone et al, 1996). A functional support network is seen as sustaining both the care recipient and the primary caregiver.…”
Section: Sociodemographic Caregiver and Relationship Predictorsmentioning
confidence: 98%
“…According to Husband (1987, in Morris et al, 1991) such a correlation is found only in female spouse carers. Robinson (1990) found past marital adjustment to be the best predictor of subjective burden among wife caregivers.…”
Section: Downloaded By [Linnaeus University] At 09:19 09 February 2012mentioning
confidence: 99%